ANALISIS EFEKTIVITAS PEMBELAJARAN DARING DI PROGRAM STUDI PENDIDIKAN EKONOMI FKIP UNIVERSITAS RIAU - Pakpahan, Santa Veronika; Gimin, Gimin; Haryana, Gani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: Due to the Covid-19 pandemic, the Indonesian government has shifted face-to-face teaching and learning activities to online learning. This study aims to analyze the effectiveness of online learning and the obstacles faced by students during online learning at the Economic Education Study Program, FKIP University of Riau. This study uses quantitative methods with descriptive statistical data analysis techniques. The subjects of this study were students of class 2017,2018,2019 who actively participated in online learning with a sample of 70 people. Quantitative data collected through online questionnaires through the google form application media. The results of data analysis in this study are where online learning can be said to be effective if it is in accordance with indicators of learning success such as learning mastery, learning activities, the ability of educators to manage learning, facilities and infrastructure that support learning. Based on the results of this study, the conclusion of this study is that the effectiveness of online learning carried out during the Covid 19 pandemic which in terms of various indicators has been running very effectively with a percentage of 75.45%. Thus, the analysis of the effectiveness of online learning carried out during the COVID-19 pandemic has been very effective. As for the obstacles faced by students, students can overcome the obstacles well.Keywords: Effectiveness, Online Learning, Indicators, Learning Constraints.